2015
DOI: 10.1128/jvi.00701-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for 2′-5′-Oligoadenylate Binding and Enzyme Activity of a Viral RNase L Antagonist

Abstract: Synthesis of 2=-5=-oligoadenylates (2-5A) by oligoadenylate synthetase (OAS) is an important innate cellular response that limits viral replication by activating the latent cellular RNase, RNase L, to degrade single-stranded RNA. Some rotaviruses and coronaviruses antagonize the OAS/RNase L pathway through the activity of an encoded 2H phosphoesterase domain that cleaves 2-5A. These viral 2H phosphoesterases are phylogenetically related to the cellular A kinase anchoring protein 7 (AKAP7) and share a core stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…The arginine that is important for stabilizing 2-5A has previously been reported to be present in the R-loop region and is also strictly conserved in those three proteins ( Fig. 2a, d) (Ogden et al, 2015). All of the aforementioned characteristics demonstrate the structural conservation of the PDE catalytic domain of these three 2H phosphoesterases, despite lacking significant sequence homology ( Fig.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The arginine that is important for stabilizing 2-5A has previously been reported to be present in the R-loop region and is also strictly conserved in those three proteins ( Fig. 2a, d) (Ogden et al, 2015). All of the aforementioned characteristics demonstrate the structural conservation of the PDE catalytic domain of these three 2H phosphoesterases, despite lacking significant sequence homology ( Fig.…”
supporting
confidence: 52%
“…2a). The structures of AKAP7 CD (PDB ID 2VFY) and VP3-CTD (PDB ID 5AF2), which exhibit substantial structural homology, have previously been determined (Brandmann & Jinek, 2015;Ogden et al, 2015). The structural alignment of ns2 7-167 , AKAP7 CD and VP3-CTD indicated that all of these structures form similar positive electrostatic concave regions in the 29,59-PDE activity domain, which is putatively involved in the binding and cleavage of 2-5A ( Fig.…”
mentioning
confidence: 96%
“…In recombinant MHV viruses, rotavirus VP3 can substitute for ns2 and rescue replication in bone marrow-derived macrophages and in mouse liver. Sequence alignments suggest that a similar PDE occurs in all group A and likely group B and C rotavirus strains [26,27].…”
Section: -5a Degradation By a Viral Phosphodiesterasementioning
confidence: 96%
“…In contrast, in RNase L knockout B6 mice, both viruses replicated similarly, suggesting that ns2 directly acts through OAS-RNase L [56]. Similarly, rotavirus A (RVA) encodes for the viral protein 3 (VP3), which is structurally homologous in its C-terminal domain to MHV-ns2 [54,57,58]. Although from evolutionarily non-related viruses, VP3 degraded 2-5A in similar manner as ns2 in vitro and in intact cells, whereas mutation of the two conserved histidines in the PDE catalytic site of VP3 prevented 2-5A degradation.…”
Section: Cellular and Viral Inhibitors Of Oas-rnase Lmentioning
confidence: 99%
“…The 2H central domain of the murine AKAP7 restored replication of ns2 mutant MHV chimeric virus whereas MHV chimeras with a histidine-to-arginine mutation in the His-X-Thr motif of AKAP7 central domain failed to replicate in bone marrow macrophages of B6 mice [61]. Due to structural homology, it was proposed that AKAP7 could be the evolutionary precursor of viral 2 0 ,5 0 PDE members [58,61]. In addition, phosphodiesterase 12 (PDE12) is a member of the exonuclease-endonuclease phosphatase family that localizes in mitochondria and regulates mRNA turnover by removing the polyA tails [62,63].…”
Section: Cellular and Viral Inhibitors Of Oas-rnase Lmentioning
confidence: 99%